Comprehensive Study on Dynamic Modulus and Road Performance of High-Performance Asphalt Mixture - Qi Liu; Jiakai Lu; Zhiqiang Zhang; Zhiang Chen; Tao Wang; Qi Zheng (Buildings)
Asphalt pavement durability significantly impacts the service life of roads, and hence, understanding the performance of high-performance asphalt mixtures is crucial. This study investigates the performance of four high-performance asphalt mixtures: heavy-load AC-20, high-viscosity AC-20, heavy-load SMA-13, and heavy-load SMA-10. Linear Amplitude Sweep (LAS) tests revealed that heavy-load asphalt mixtures exhibit superior fatigue resistances, with the fatigue life of heavy-load SMA-13 exceeding 1.5 times that of high-viscosity AC-20 under similar stress levels. Bending Beam Rheometer (BBR) tests at −6 °C, −12 °C, and −18 °C demonstrated that both heavy-load and high-viscosity asphalts had comparable low-temperature crack resistance, with heavy-load SMA-13 showing a stiffness modulus of 627 MPa at −18 °C. Marshall tests indicated that heavy-load AC-20 had the highest stability (14.3 kN) among the tested mixtures, while heavy-load SMA-13 exhibited the highest density (2.603 g/cm3). Dynamic modulus tests spanning a frequency range of 10−4 Hz to 105 Hz at various temperatures showed that heavy-load SMA-13 had a higher dynamic modulus than heavy-load SMA-10, particularly at lower frequencies (higher temperatures). Rutting tests at 60 °C indicated that heavy-load SMA-13 had the lowest rut depth (18.5 mm), outperforming other mixtures by up to 25%. The heavy-load SMA-13 asphalt mixture demonstrated the best overall performance, especially in terms of high-temperature stability, fatigue resistance, and rutting resistance. This study provides essential material performance parameters for the development of durable high-performance asphalt pavement structures.